2018
DOI: 10.1051/epjconf/201818002030
|View full text |Cite
|
Sign up to set email alerts
|

The influence of distance between vehicles in platoon on aerodynamic parameters

Abstract: Abstract. The paper presents the results of experimental and numerical research focused on the reduction of fuel consumption of vehicles driving one after another in a so-called platoon arrangement. The aerodynamic parameters and safety issues were analyzed in order to determine the optimal distance between the vehicles in traffic conditions. The experimental research delivered the results concerning the drag and was performed for simplified model of two vehicles positioned in wind tunnel equipped with aerodyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 12 publications
3
12
0
Order By: Relevance
“…They showed that the increase in drag of the follower of two in-line Ahmed bodies is due to significant changes in the wake structure between the bodies, as spacing ratio increased from 0.5 to 1.0. Gnatowska and Sosnowski [27] also made similar conclusions based on results from experiments and Reynolds Averaged Navier-Stokes (RANS)-based turbulence modelling. In a recent study, Murzyn et al [10] performed detailed two-dimensional (2D) laser Doppler velocimetry (LDV) measurements of the wake structure between two Ahmed bodies using six spacing ratios ranging from 0.25 to 1.53 and three slant angles, α = 0 • , 25 • and 35 • .…”
Section: Introductionsupporting
confidence: 56%
“…They showed that the increase in drag of the follower of two in-line Ahmed bodies is due to significant changes in the wake structure between the bodies, as spacing ratio increased from 0.5 to 1.0. Gnatowska and Sosnowski [27] also made similar conclusions based on results from experiments and Reynolds Averaged Navier-Stokes (RANS)-based turbulence modelling. In a recent study, Murzyn et al [10] performed detailed two-dimensional (2D) laser Doppler velocimetry (LDV) measurements of the wake structure between two Ahmed bodies using six spacing ratios ranging from 0.25 to 1.53 and three slant angles, α = 0 • , 25 • and 35 • .…”
Section: Introductionsupporting
confidence: 56%
“…Advances in aerospace, power engineering [19,20], automotive [21,22], civil engineering [6,23,24], medicine [25,26] and other numerous branches of the industry could not have been achieved without the application of computational methods as a research tool. The primary and critical activity in numerical modelling is the computational domain discretization.…”
Section: Computational Domain Discretizationmentioning
confidence: 99%
“…The research performed concerns the application of the above ical methods to investigate the drag coefficient of a vehicle model. Research into aerodynamic parameters of a single vehicle as well as arrangement of subs quent vehicles driving in a so-called platoon are carried out in the automotive o reduce the fuel consumption and in consequence increase the efficiency of the analyzed design [17]. Therefore research dedicated to the estimation of the influence of computational domain discretization on CFD results concerning the aerodynamics of a vehicle are purposeful.…”
Section: A)mentioning
confidence: 99%
“…The research object is a vehicle model described in [17] and commonly called the AHMED body. It is one of the most popular models used as a simplified vehicle shape to predict the fundamental flow physics associated with a vehicle wake.…”
Section: The Numerical Setupmentioning
confidence: 99%
See 1 more Smart Citation